2011
DOI: 10.2175/106143011x13075599870216
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated with Wastewater Treatment, Reuse, and Disposal

Abstract: A review of the literature published in 2010 on topics relating to the public and environmental health risks associated with wastewater treatment, reuse, and disposal is presented. This review is divided into the following sections: wastewater treatment and management, ecological impacts and ecotoxicology, potable reuse, nonpotable reuse, and wastewater disposal and discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…85 Several studies have also observed seasonal patterns of higher discharge of pharmaceuticals and personal care products in wastewater effluent during low flow and less during high flow periods. 86,87 While increasing research attention and regulatory efforts have been devoted to understanding prevalence of nonconventional chemical constituents in WWTPs and in receiving environments, 88 studies specifically focusing on characterization and risk assessment of emerging chemical constituents of concern in the context of recycled water applications are limited. [89][90][91] Advanced oxidation processes are particularly promising for removal of these pharmaceuticals and other organic compounds (Table 5).…”
Section: Chronic Contaminantsmentioning
confidence: 99%
“…85 Several studies have also observed seasonal patterns of higher discharge of pharmaceuticals and personal care products in wastewater effluent during low flow and less during high flow periods. 86,87 While increasing research attention and regulatory efforts have been devoted to understanding prevalence of nonconventional chemical constituents in WWTPs and in receiving environments, 88 studies specifically focusing on characterization and risk assessment of emerging chemical constituents of concern in the context of recycled water applications are limited. [89][90][91] Advanced oxidation processes are particularly promising for removal of these pharmaceuticals and other organic compounds (Table 5).…”
Section: Chronic Contaminantsmentioning
confidence: 99%
“…In fact, about one tenth of global crops was irrigated with sewage; unfortunately, in which only 10 % was properly treated (World Bank, important issue must be considered is the existence of emerging pollutants such as phthalates, polychlorobiphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), pharmaceutical compounds, personal care products, etc (Peterson et al, 2011). Since the compounds may enter the food chain through bioaccumulation and biomagnification, the utilization of reclaimed water should follow proper standards (Peterson et al, 2011). With more stringent regulations on the quality of irrigated water, the market of effluent reclamation for agriculture would be encouraging (Mekala et al, 2008;Yi et al, 2011).…”
Section: Water-reuse Marketmentioning
confidence: 99%
“…The research themes were very diverse, ranging from its applications and advantages (Guest et al, 2009); treatment technologies and operational issues (de Koning et al, 2008;Venkatesan et al, 2011); economics of water reuse (Daniels and Porter, 2012;Listowski et al, 2013;Molinos-Senante et al, 2011) to its impacts on the environment, public health and safety (Peterson et al, 2011;Rose, 2007;Zhang et al, 2011) as well as social reactions of end-users (Hartley, 2006;Po et al, 2003;Russell and Hampton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A stabilization pond is the most simple, reliable and cost-effective process with low maintenance requirements that can be used as an appropriate alternative for wastewater treatment by reducing biological oxygen demand (BOD 5 ) (3). Inappropriate operation of a waste water treatment systems may result in severe environmental and public health problems, as its effluent to a receiving water body can cause or spread various diseases to human beings (4). The performance of a WSP is often affected by various factors such as physical and biological factors (5).…”
Section: Introductionmentioning
confidence: 99%